Simulation Study of Bilayer Absorber Perovskite Solar Cells Using SCAPS-1D - Hachachen Abir; Dridi Nadjoua (University of Shahid Hama Lakhdar - El Oued, 2024)
In recent years, perovskite-based solar cells have seen significant development and widespread interest due to their high efficiency and stable performance. In this thesis, the CsPbIBr2/KSnI3 bilayer perovskite solar cell was studied through numerical simulation using the SCAPS-1D simulation program. In the first step of this work, the reference structure of the solar cell FTO/SnO2/CsPbIBr2/Spiro/Au was studied and simulated to verify the accuracy of the simulation and the compatibility of the obtained results with experimental data. We achieved an efficiency of 9.70%, which is highly consistent with experimental cells. To enhance the cell's efficiency, a new absorber material, KSnI3, was added as a bottom absorber layer, contributing to the broadening of the cell's absorption range. This resulted in the new structure FTO/SnO2/CsPbIBr2/KSnI3/Spiro/Au, which significantly increased the efficiency compared to the first structure that relies on a single absorber layer, with the cell efficiency reaching approximately 16.9%. In the next step, we studied the effect of some key parameters such as the thickness and doping concentration of the two absorbers to improve the CsPbIBr2/KSnI3 bilayer perovskite solar cell. The best efficiency obtained was a PCE of 19.89% for thicknesses of 700 and 1000 nanometers and doping concentrations of 1x1015 and 1x1016 cm-3 for the dual absorber layers CsPbIBr2 and KSnI3, respectively. Finally, we studied the effect of temperature on the efficiency of the optimized solar cell within the range of 260-350 Kelvin. The simulation results showed that efficiency decreases at very high temperatures. في السنوات الاخيرة عرفت الخلايا الشمسية القائمة على بيروفسكايت تطور كبير و إهتمام واسع بسبب الكفاءة العالية والاستقرار في الاداء لهذا النوع. في هذه المذكرة تم دراسة الخلية الشمسية بيروفسكايت ثنائية الطبقة الماصة 3KsnI/2CsPbIBr بواسطة محاكاة رقمية باستخدام برنامج المحاكاة 1D -. SCAPS في الخطوة الاولى من هذا العمل تمت دراسة ومحاكاة هيكل مرجعي للخلية الشمسية Au Spiro//2CsPbIBr/2FTO/SnO وذلك للتحقق من صحة المحاكاة وتوافق النتائج المتحصل عليها مع البيانات التجريبية. تحصلنا على مردود يقدر ب % 9.70 وهاته النتيجة تتوافق بشكل كبير مع الخلايا التجريبية . من أجل الرفع من كفاءة الخلية تم اضافة مادة ماصة جديدة 3KsnI بمثابة طبقة ماصة سفلية والتي تساهم في توسيع نطاق الامتصاص للخلية ليصبح الهيكل الجديد من الشكل Spiro/Au /3KsnI/2CsPbIBr/2FTO/SnO وقد ساهمت هذه الاضافة في رفع الكفاءة بشكل كبير مقارنة بالهيكل الأول الذي يعتمد على طبقة ماصة واحدة حيث أصبح مردود الخلية يقارب % 16.9. في الخطوة التالية قمنا بدراسة تأثير بعض المعلمات الأساسية مثل السمك وتركيز التطعيم للمادتين الماصتين وذلك من أجل تحسين الهيكل القائم عن الطبقتين الماصتين 3KsnI/2. CsPbIBr أحسن مردود تم الحصول عليه هو % 19.89 وذلك من اجل سمك 700 و 1000 نانومتر و كذلك بتركيز 3-cm 1610x 1 و 3-cm 1510 x 1 لثنائي الطبقة الماصة 3KSnI/2CsPbIBr علي الترتيب . واخيرا درسنا تأثير درجة الحرارة على كفاءة الخلية الشمسية المحسنة في المجال المحصور من 260 - 350 كلفن وقد بينت نتائج المحاكاة ان الكفاءة تنخفض عند درجات الحرارة العالية جدا
Master's theses: specializing in wired and non-wired communications
Keywords: Bilayer absorber; Perovskite solar cell; Wide bandgap; CsPbIBr2; PCE; SCAPS-1D.; ممتص ثنائي الطبقة، خلية بيروفسكايت الشمسية، فجوة نطاق واسعة، 2CsPbIBr ، PCE ، 1D-SCAPS